Multi-wavelength Q-switched Erbium-doped fiber laser with photonic crystal fiber and graphene – Polyethylene oxide saturable absorber - Tiu, Z.C.; Ahmad, F.; Tan, S.J.; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2015)
A simple multi-wavelength passively Q-switched Erbium-doped fiber laser is demonstrated using graphene based saturable absorber, which is prepared using polyethylene oxide as a host polymer. The multi-wavelength operation is achieved based on nonlinear polarization rotation effect by incorporating 50 m long photonic crystal fiber in the ring cavity. The Erbium-doped fiber laser produces a stable wavelength oscillation for more than 10 lines and fixed spacing of 0.46 nm. The Erbium-doped fiber laser also demonstrates a stable pulse train with the repetition rate increases from 14.6 to 16.3 kHz as the pump power increases from the threshold power of 39.6 mW to the maximum pump power of 46.8 mW. The minimum pulse width of 1.2 μs was obtained at the maximum pump power of 46.8 mW while the highest energy of 1.57 nJ was obtained at pump power of 39.6 mW.